Pengaruh Kemampuan Mengajar Guru Pendidikan Agama Islam terhadap Perilaku Keagamaan Siswa - Muqit, Ade Abdul; Maskur, Abu (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2022)
The teaching ability of teachers is one of the benchmarks for the quality of the learning process, because teachers have a very important role in shaping student behavior, including religious behavior. This study seeks to reveal the effect of PAI teachers' teaching abilities on the religious behavior of students at SD Al-Bayan Islamic School, South Tangerang. This research is a quantitative research with data collection techniques using a questionnaire (questionnaire) distributed to 100 respondents. The results of this study indicate that there is a positive and strong influence between the teaching ability of PAI teachers on the religious behavior of students at SD Al-Bayan Islamic School South Tangerang which is expressed by the equation, = 16,941 + 0.713 X2, meaning that every time there is an increase in the teacher's teaching ability score. PAI, it will be followed by an increase in the religious behavior of students by 0.713. The magnitude of the contribution of the relationship between the teaching ability of PAI teachers and the religious behavior of students is determined by the coefficient of partial determination between the teaching ability of teachers and the religious behavior of students, r2 of 0.598 or 59.8%. This shows that the contribution of the teacher's teaching ability to the improvement of the religious behavior of the students of SD Al-Bayan Islamic School Tangerang is 59.8%.